TINGKAT PERUBAHAN KUALITAS BAKSO DAGING SAPI BALI BAGIAN SANDUNG LAMUR (Pectoralis profundus) SELAMA PENYIMPANAN DENGAN PEMBERIAN ASAP CAIR - -, Astati (Fakultas Sains dan Teknologi UIN ALauddin, 2013)
This study aimed to determine the effect of storage duration and level of liquid smoke on quality of meatballs from Bali beef section brisket (Pectoral is profundus). The research methodology is based on completely randomized design (CRD) with a general pattern that is 3 x 4 with 3 replications, for cooking shrinkage test consisted of 3 treatments and 3 replications, and organoleptic test used for pattern 3 x 3 with 3 replications. Composition of treatment as follows: The first factors is the level of liquid smoke to the A1 (0% by weight of liquid smoke meat in dough), A2 (1% by weight of liquid smoke meat in the dough) and A3 (2% by weight of liquid smoke meat in dough). Factor II is with B1 storage time (1 week), B2 (2 weeks), B3 (3 weeks) and B4 (4 weeks). Data were analyzed with analysis of range by using completely randomized design (CRD) consisting of 6 parameters of quality testing meatballs using the Least Significant Difference Test (BNT). Based on the analysis and discussion of the variety it can be concluded that the level of liquid smoke does not affect the quality of meatballs while the storage time eeffects the quality of the balls except the resilience parameter.Keywords : Quality of Meatballs, Muscles Pectoralis profundus, Liquid Smoke and Old Storage